Comparison of physical activity between children with autism spectrum disorders and typically developing children - Bandini, Linda G.; Gleason, James; Curtin, Carol; Lividini, Keith; Anderson, Sarah E.; Cermak, Sharon A.; Maslin, Melissa; Must, Aviva (SAGE Publications, 2013)
Regular physical activity is important for promoting health and well-being; however, physical activity behaviors in children with autism spectrum disorders (ASD) have received little attention. We compared physical activity levels among 53 children with ASD and 58 typically developing children aged 3–11 years who participated in the Children’s Activity and Meal Patterns Study (CHAMPS). After adjustment for age and sex the amount of time spent daily in moderate and vigorous activity was similar in children with ASD (50.0 minutes/day and typically developing children 57.1 minutes/day). However, parents reported that children with ASD participated in significantly fewer types of physical activities than did typically developing children (6.9 vs. 9.6, p <.0001) and spent less time annually participating in these activities than typically developing children (158 vs. 225 hours per year, p < 0.0001) after adjusting for age and sex. Although both groups of children engaged in similar levels of moderate and vigorous activity as measured by accelerometry, children with ASD engaged in fewer physical activities and for less time according to parental report, suggesting that some of the activity in children with ASD is not captured by standard questionnaire-based measures.